Hydrocarbon degradation abilities of psychrotolerant Bacillus strains - Kolsal, Fulya (AIMS Microbiol, 2017)
Biodegradation requires identification of hydrocarbon degrading microbes and the investigation of psychrotolerant hydrocarbon degrading microbes is essential for successful biodegradation in cold seawater. In the present study, a total of 597 Bacillus isolates were screened to select psychrotolerant strains and 134 isolates were established as psychrotolerant on the basis of their ability to grow at 7 °C. Hydrocarbon degradation capacities of these 134 psychrotolerant isolate were initially investigated on agar medium containing different hydrocarbons (naphthalene, n-hexadecane, mineral oil) and 47 positive isolates were grown in broth medium containing hydrocarbons at 20 °C under static culture. Bacterial growth was estimated in terms of viable cell count (cfu ml(−1)). Isolates showing the best growth in static culture were further grown in presence of crude oil under shaking culture and viable cell count was observed between 8.3 × 10(5)–7.4 × 10(8) cfu ml(−1). In the final step, polycyclic aromatic hydrocarbon (PAH) (chrysene and naphthalene) degradation yield of two most potent isolates was determined by GC-MS along with the measurement of pH, biomass and emulsification activities. Results showed that isolates Ege B.6.2i and Ege B.1.4Ka have shown 60% and 36% chrysene degradation yield, respectively, while 33% and 55% naphthalene degradation yield, respectively, with emulsification activities ranges between 33–50%. These isolates can be used to remove hydrocarbon contamination from different environments, particularly in cold regions.